2020
DOI: 10.1002/aps3.11383
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of black Sigatoka in banana leaves using hyperspectral images

Abstract: Premise Black Sigatoka is one of the most severe banana (Musa spp.) diseases worldwide, but no methods for the rapid early detection of this disease have been reported. This paper assesses the use of hyperspectral images for the development of a partial‐least‐squares penalized‐logistic‐regression (PLS–PLR) model and a hyperspectral biplot (HS biplot) as a visual tool for detecting the early stages of black Sigatoka disease. Methods Young (three‐month‐old) banana plants were inoculated with a conidia suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Many of these studies have shown the efficacy of supervised methods such as partial least squares discriminant analysis (PLS-DA) [52,[84][85][86] and machine learning algorithms such as Random Forest [87][88][89][90] in identifying more significant environmental variables and predicting susceptibility levels with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have shown the efficacy of supervised methods such as partial least squares discriminant analysis (PLS-DA) [52,[84][85][86] and machine learning algorithms such as Random Forest [87][88][89][90] in identifying more significant environmental variables and predicting susceptibility levels with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared spectroscopy (NIRs) is an emerging method that is both rapid and nondestructive [8]. It is used for qualitative and quantitative analysis of the chemical composition of fruits such as apples [9], bananas [10], peaches [11], kiwifruits [12], and pears [13]. Tis method is becoming increasingly popular as a solution to the limitations and challenges of traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…When the conveyor belt moves horizontally, the hyperspectral camera can collect the hyperspectral image of the measured object (Xu et al., 2020). This method has good applicability to the measured objects on the collection plane, such as meat (Zhang et al., 2022) and leaves (Chen et al., 2020; Ugarte Fajardo et al., 2020). However, there are two difficulties in the detection of surface defects of spherical fruit (usually considered Lambertian objects, i.e., a completely diffuse reflection object).…”
Section: Introductionmentioning
confidence: 99%